Antiretroviral therapy and associated drug interactions with cardiovascular drugs: a critical review - Spanakis, Marios; Alexakis, Konstantinos; Ioannou, Petros (Frontiers in Pharmacology, 2025)
The significant progress in HIV research has led to the development of innovative medicines and protocols. Most people living with HIV (PLWH) achieve longer lifespans when adhering strictly to the therapeutic protocols. A notable characteristic of PLWH is a higher incidence of cardiovascular diseases. This may result from the disease itself or increased life expectancy. Regardless of the underlying cause, it often requires the concurrent use of antiretroviral therapy (ART) and cardiovascular disease (CVD) medications. In such cases, a key issue regarding optimal evidence-based practices is the management of potential and clinically significant drug–drug interactions (DDIs). Over time, our understanding of DDIs has advanced significantly. These advancements have led to the development of tools and approaches for identifying and managing DDIs, especially in special population groups such as PLWH. Clinically, recognizing and managing these interactions is key to preventing adverse effects and optimizing outcomes in PLWH, thereby enhancing patient safety and quality of care. This review discusses the latest data on DDIs between ART and CVD medications, emphasizing their clinical significance. Furthermore, it explores how established tools, such as the Liverpool Drug Interaction Checker and Lexidrug®, can support healthcare professionals. Combined with insights from the literature and summaries of product characteristics, these tools can guide the identification and management of DDIs between ART and CVD medications to ensure optimal therapeutic outcomes.